Differential gene expression analysis in early and late erythroid progenitor cells in ß-thalassaemia - Forster, L.; McCooke, J.; Bellgard, M.; Joske, D.; Finlayson, J.; Ghassemifar, Reza (Blackwell Publishing Ltd, 2015)
ß- thalassaemia is a disorder of globin gene synthesis resulting in reduced or absent production of the ß-globin chain in red blood cells. In this study, haematopoietic stem cells were isolated from the peripheral blood of six transfusion dependent ß-thalassaemia patients and six healthy controls. Following 7 and 14 d in culture, early- and late- erythroblasts were isolated and purified. No morphological difference in maturation was observed following 7 d in culture, while a delayed maturation was observed in the patient group after 14 d. Following RNA isolation and linear amplification, gene expression analyses were performed using microarray technology. The generated data were analysed by two methods: the BRB-ArrayTools platform and the Bioconductor platform using bead level data. Following 7 d culture, there was no difference in gene expression between the control and patient groups. Following 14 d culture, 384 differentially expressed genes were identified by either analysis. A subset of 90 genes was selected and the results were confirmed by Quantitative-Real-Time-polymerase chain reaction. Pathways shown to be significantly altered in the patient group include apoptosis, MAPKinase and the nuclear factor-KB pathway.